Religious Moderation in Indonesia: Implementation by National Christian Institution to Strengthen National Resilience - Kaur, Kumari Nihal; Puspitasari, Maria (Technium Social Sciences Journal, 2024)
Religious moderation is a program introduced by the Indonesian Ministry of Religious Affairs to promote unity and harmony as a response to frequent intolerance incidents in the country that risks national resilience. This research begins by identifying how religious moderation is poured into a nationwide strategy through a presidential regulation and Ministry of Religious Affairs’ roadmap, which then progresses to how PGI as a Christian organisation implements religious moderation into their own strategy. The results of this research suggest that PGI has contributed to religious moderation for decades by initiating interfaith networks, launching tolerance programs and advocating vulnerable groups. These measures are considered as coping and adaptive strategies in strengthening national resilience but have yet to touch on a transformative level that would be deemed more effective as intolerance incidents are still recurring in the present.